Treatment goals in ANCA-associated vasculitis: defining success in a new era - Alberici, Federico; Tedesco, Martina; Popov, Tamara; Balcells-Oliver, Monica; Mescia, Federica (Frontiers in Immunology, 2024)
Health-related quality of life is a key contributor to overall well-being, and this is becoming an increasingly prominent factor when making therapeutic choices in the management of ANCA-associated vasculitis (AAV). Progress in available therapeutic strategies for AAV has resulted in this historically acute disease with a potentially fatal short-term outcome, becoming a relapsing-remitting chronic disorder. This new perspective on AAV means that patient survival should no longer be considered as the only major treatment target. Additional outcomes in this context that should be portrayed in order to consider a therapeutic approach as successful include patient quality of life, as well as the burden of treatment-induced morbidity. Comorbidities and impaired quality of life in patients with AAV, as with many other autoimmune diseases, may be a consequence of the disease itself as well as a result of the therapy employed. The AAV disease process may induce organ damage, including kidney failure and structural lung damage, and increase the risk of cardiovascular disease. On top of this, treatments employed to manage the disease may contribute further to the overall comorbidities burden. Furthermore, pre-existing comorbidities can increase AAV severity and may also be contraindications that limit potential therapeutic options. Quality of life is another central topic that can have a huge impact on patient wellbeing as well as adherence to treatment. Ongoing monitoring of comorbidity risk and of quality of life is thus key for successful AAV management. This process, however, may be complicated; the identification of the correct parameters on which to focus is not always straightforward and, more importantly, it is sometimes the symptoms that may appear trivial to physicians that are most detrimental to a patient’s quality of life. With these shifts in treatment capabilities and understanding of patient burden, it is necessary to adjust the treatment paradigm accordingly. Treatment success is no longer defined solely by the control of disease activity; treatment success requires holistic improvement determined through the assessment of all aspects of the disease, ranging from disease control to comorbidity risk through to the assessment of health-related quality of life. This review explores the burden of AAV itself as well as treatment-related side effects with a special focus on the tools available to measure outcomes. The management of AAV has entered a new era with a strong focus on both the management and prevention of comorbidities as well as patient-reported outcomes, both of which are now considered key factors in defining treatment success.